The Influence of Government Regulation on Waste Reduction Among Kuantan Malaysian Construction Industry - Nurushshahirah, Sabodin; Adeleke, A. Q. (Penerbit Akademia Baru, 2018)
This paper examined the significant relationship between government regulation and construction waste management among Malaysian construction industries. Survey was conducted among 10 contractors registered G7, using proportionate stratified random sampling, out of which 10 questionnaire were collected for data analysis with five point Likert scale categories of waste management from previous studies, statistical analysis affirmed a significant positive relationship between government regulation and construction waste management in Malaysian construction industries through Statistical Package for the Social Sciences